PROTOTYPE DESIGN OF TIMBULREJO VILLAGE DEVICE PERCENTAGE SYSTEM BASED ON QR CODE - Mardiyanto Mardiyanto; Maretha Rahmawati (Jurnal TAM (Technology Acceptance Model), 2021)
QR code is a two-dimensional matrix code as a development of the evolution of barcode codes, the present system is an important thing in every office and other institution to see the results of attendance. Modern era like today by creating a QR Code persistence system with the concept of BYOD (Bring Your Own Devices), so that the percentage system becomes more modern. The village apparatus percentage system aims to form the discipline of the Timbulrejo Village Apparatus, and is useful for accelerating and facilitating absentee reporting to be more effective and efficient. Using the Prototype method to describe the system, the user or system owner has a picture of the system development that will be carried out, using Fishbone and context diagrams, to describe the analysis and design of the system. The process of collecting data is by observing, interviewing, and studying literature. In making this or code-based persistence system using the PHP MySQL programming language so that the system can be made according to the design, such as the home page, the admin menu which consists of the dashboard menu, the data menu which contains data for village apparatus and its offices, the menu for the Village hall and the menu. weekdays, then there is a menu to take a QR Code and scan a QR Code, a menu of attendance data which consists of a menu of history and presentation recap, finally, there is a set menu consisting of user management and menu management the resulting system is expected to greatly facilitate all users